A formação continuada nas semanas pedagógicas de fevereiro no período 2007-2013 no estado do Paraná - Tessari, Elisabete Valdira de Sousa (2015)
This dissertation is analyzed the Pedagogical Weeks of February as continued training modality offered in Paraná. The overall objective was to assess the continuing education of teachers offered at the Pedagogical Week format February Parana, during the governments Roberto Requião Mello e Silva (2007-2010) and Carlos Alberto Richa (2011-2013). Through the guiding documents of the Pedagogical Weeks we sought to understand the actions of these governments what they bring as education proposal, as is projected continuing education of teachers during the Pedagogical Weeks, the actions developed at school for this purpose, the construction of knowledge and design of education and society, since the ideological lines of these governments seemed to differ. To arrest the general objective of the research, we formulate specific objectives that have guided our research: to present the educational legislation concerning the continuing education of teachers; discuss the different denominations and concepts that continued training received in official documents and authors who discuss the subject; and present a analyze the guiding documents of the Pedagogical Weeks of February 2007-2013, taking as its starting point the categories Political and Educational Project, curriculum, pedagogical work of the Organization and School Management. The survey of theoretical nature, is based on bibliographical and documentary analysis. In this sense, we have established dialogue with authors who have been discussing the issue and have helped us to understand the idea of public policy for continuing education of teachers, they are organized using public resources, its technical and financial limits, its contradictions, its possible limits or contributions to improving the quality of public education in Paraná. The management of Roberto Requião presented overcoming announcement of neoliberal policies implemented by his predecessor Jaime Lerner, who remained the guiding documents of the Pedagogical weeks. We came to the realization that the advertised speech was riddled with contradictory character, though, concomitantly there was an effort by SEED in overcoming the neoliberal educational model, with a Pedagogical Week proposal more consistent when it comes to understanding the curriculum, PPP, School management and Pedagogical Work Organization. The management Beto Richa and her 'the way of governing', brought in referring the guiding documents of the Pedagogical weeks the resumption of neoliberal education policy principles and transfers for weeks Pedagogical formative space the proposed training with managerial, motivational molds, constant monitoring in an attempt to resume the pedagogy of projects, implementation of a formal instrument of systematic evaluation for all SAEP state, disregarding the federal instrument SAEB, a ranking proposition of the state's schools and merit-based process